RASA1 somatic mutation and variable expressivity in capillary malformation/arteriovenous malformation (CM/AVM) syndrome. Issue 6 (11th March 2016) - Macmurdo, Colleen F.; Wooderchak‐Donahue, Whitney; Bayrak‐Toydemir, Pinar; Le, Jenny; Wallenstein, Matthew B.; Milla, Carlos; Teng, Joyce M. C.; Bernstein, Jonathan A.; Stevenson, David A.
Abstract : Germline mutations in RASA1 are associated with capillary malformation‐arteriovenous malformation (CM‐AVM) syndrome. CM‐AVM syndrome is characterized by multi‐focal capillary malformations and arteriovenous malformations. Lymphatic anomalies have been proposed as part of the phenotype. Intrafamilial variability has been reported, suggesting modifiers and somatic events. The objective of the study was to identify somatic RASA1 "second hits" from vascular malformations associated with CM‐AVM syndrome, and describe phenotypic variability. Participants were examined and phenotyped. Genomic DNA was extracted from peripheral blood on all participants. Whole‐exome sequencing was performed on the proband. Using Sanger sequencing, RASA1 exon 8 was PCR‐amplified to track the c.1248T>G, p.Tyr416X germline variant through the family. A skin biopsy of a capillary malformation from the proband's mother was also obtained, and next‐generation sequencing was performed on DNA from the affected tissue. A familial germline heterozygous novel pathogenic RASA1 variant, c.1248T>G (p.Tyr416X), was identified in the proband and her mother. The proband had capillary malformations, chylothorax, lymphedema, and overgrowth, while her affected mother had only isolated capillary malformations. Sequence analysis of DNA extracted from a skin biopsy of a capillary malformation of the affected mother showed a second RASA1 somatic mutation (c.2245C>T, p.Arg749X). These results and the extreme variable expressivity support the hypothesis that somatic "second hits" are required for the development of vascular anomalies associated with CM‐AVM syndrome. In addition, the phenotypes of the affected individuals further clarify that lymphatic manifestations are also part of the phenotypic spectrum of RASA1 ‐related disorders. © 2016 Wiley Periodicals, Inc.